Hybrid Calcifying Epithelial Odontogenic Tumor and Ameloblastoma: A Report of an Extremely Rare Condition: Hybrid Calcifying Epithelial Odontogenic and Ameloblastoma Tumor: Hybrid Calcifying Epithelial Odontogenic and Ameloblastoma Tumor - Ekrampoor, Mohammad Saleh; Daneste, Hossein; Amiri, Mohammad Amin (Galen Medical Journal, 2023)
Calcifying epithelial odontogenic tumor (CEOT) and ameloblastoma are types of odontogenic tumors accounting for 1%, and 10% of all the odontogenic tumors. While sharing same odontogenic origin, these tumors are found to exhibit distinct clinicopathological features. In the present study, we present the third hybrid CEOT/Ameloblastoma tumor ever reported. The current CEOT/Amelobastoma is occurred after a previously operated CEOT in the same area. The patient was refered with distict clinical features of swelling and paresthesia. In the radiographic examination, a unilocular lesion with mixed internal structure and ambiguous periphery was seen which exhibited buccal and lingual cortical expansion, thining, and perforation as well as inferior alveolar canal perforation. The histopathology results suggested a CEOT/Ameloblastoma lesion. After the tumor removal, the patient was set up for further follow-ups and maxillofacial prosthesis.